Bacterial infections in COVID-19 patients and their possible treatments. A review - A'liyatur Rosyidah; Mohamad Padri; Paulus Damar Bayu Murti (The East Java Biological Society, 2021)
The COVID-19 pandemic, which started in the beginning of 2020 was triggered by a new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections, severely affected various sectors, especially health. The effect of COVID-19 on patients is exacerbated by bacterial co-infections and secondary bacterial infections. There are few studies on how bacterial co-infections and secondary bacterial infections worsen COVID-19 patients, including in Indonesia. Therefore, it is necessary to update and summarize the understanding of bacterial infections characteristics to help optimize the diagnosis, prevention, and treatment decisions. Antibiotics have been used in COVID-19 patients to treat bacterial infections to date, which could contribute to antimicrobial resistance in the future. The review's objective is to summarize bacterial infections in COVID-19 patients and several possible treatments, including antibiotics, phage therapy, probiotics/prebiotics, and nanomedicine for antimicrobial peptides (AMPs) delivery